Dual Focus of Supply Chain Resilience and Sustainability: A Size-based Comparison between SMEs and Large Organizational Approaches - Simon, Dániel (International Journal of Engineering and Management Sciences, 2025)
The research investigates how organizational size influences the implementation of supply chain resilience and sustainability practices. While resilience and sustainability are increasingly recognized as interrelated priorities, existing literature often overlooks how firm size conditions strategic behaviour, particularly the distinct constraints faced by small and medium-sized enterprises (SMEs). To address this gap, the study employs a two-phase, mixed-methods approach. First, a structured literature review identifying the current state of academic research on the field. Second, a global survey of 252 supply chain professionals captures quantitative data across SMEs and large organizations. Statistical analysis tests three hypotheses regarding core aspects of driving resilience and sustainability outcomes. Findings show that large firms tend to formalize strategies more thoroughly, especially in risk detection and sustainability goal setting. However, SMEs demonstrate comparable resilience through informal, agile approaches and supplier collaboration. Overall, strategic effectiveness does not vary by firm size, but implementation pathways do. This study contributes original empirical evidence to the limited comparative literature on organizational size in supply chain strategy. By introducing size as a moderating variable, the research advances theoretical models and highlights the need for differentiated tools, policies, and partnerships. The findings aim to hold practical value for managers, and support businesses seeking to design scalable, inclusive approaches that enhance resilience and sustainability across the entire supply chain spectrum.